ANALISIS NILAI GOTONG ROYONG PADA SISWA SEKOLAH DASAR MELALUI SENI RITUAL LARUNGAN - Charina Dwi Yuliastuti; Cicilia Ika Rahayu Nita; Andika Gutama (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
This study aims to analyze the implementation of the Larungan ritual art as a learning medium in instilling the value of mutual cooperation (gotong royong) among fifth-grade elementary school students. This research employed a qualitative descriptive method, with data collected through observation, interviews, and documentation, and analyzed using the Miles and Huberman model consisting of data collection, data reduction, data display, and conclusion drawing, while data validity was ensured through technique and source triangulation. The results show that the integration of the Larungan ritual art in learning activities under the theme of Cultural Diversity creates contextual and meaningful learning experiences. Students demonstrated positive changes, including increased enthusiasm, improved cooperation in group activities, and the development of social concern and solidarity as reflections of the value of mutual cooperation. Supporting factors include school support for the use of local culture as a learning resource, students’ enthusiasm, and a coastal cultural environment that continues to preserve the Larungan tradition, while the main obstacles are limited instructional time and teachers’ readiness to integrate cultural values into learning. Overall, the implementation of the Larungan ritual art contributes positively to character education, particularly in strengthening the value of mutual cooperation.